Laser altimeter data obtained over sea-ice during the ARK-XII campaign in Jul-Sep, 1996; profile ARK-XII_SBLA_19960826T1017_80.76_146.48_thr06_data_Vers5 - Christian Haas; Stefan Hendricks; Thomas Krumpen (PANGAEA, 2024)
Sea ice surface roughness data were obtained during the ARK-XII campaign in Jul-Sep, 1996 with a Single Beam Laser Altimeter (SBLA) mounted on an/a Helicopter (Mil MI-8) . A method developed by Hibler (1972) was used to a) isolate the surface profile from low-frequency variations associated with the aircraft motion and b) to identify pressure ridge sails. The processing steps are described in https://epic.awi.de/id/eprint/56364/. We applied a ridge detection threshold of 0.6 m, which means that only sails higher 0.6 m are detected. Version and name of the processing routine: Laser_Altimeter_Processing_VS5_06_20.py (vers.5, Feb 22, 2024, https://gitlab.awi.de/sitem/sbla_processing.git). SBLA records (IBEO - PS100E) are provided at a sampling rate of 200 Hz. Sensor accuracy is 3 cm with a beam diameter at surface of 11.4 cm. This specific dataset was obtained on 19960826T1017. It includes recorded altimeter readings, the derived surface elevation and width/height/spacing of detected pressure ridge sails. Note on data quality: 11.4 cm . File name: [DMS/PANGAEA Campaing Identifier] + [DEVICE] + [DATE/TIME] + [LAT/LON] + [Detection Threshold] + [Object] + [Version] + [Format]
In: Haas, C et al. (2024): Laser altimeter data obtained over sea-ice during the ARK-XII campaign in Jul-Sep, 1996 [dataset publication series]. PANGAEA, https://doi.org/10.1594/PANGAEA.969539